1999
DOI: 10.1155/1999/716047
|View full text |Cite
|
Sign up to set email alerts
|

Differential Yield of Pathogens from Stool Testing of Nosocomial versus Community‐Acquired Paediatric Diarrhea

Abstract: OBJECTIVES:To evaluate the role of routine stool examination for all pathogens in paediatric nosocomial diarrhea (NAD) and community-acquired diarrhea (CAD) over a two-year period at Alberta Children's Hospital and current practices in other Canadian hospitals. A secondary objective was to characterize features that may predict NAD or CAD etiology. STUDY DESIGN: Retrospective cohort study and telephone survey. SETTING: Alberta Children's Hospital (retrospective review) and Canadian tertiary care paediatric cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Despite the increasing incidence of CDI among the paediatric population [ 33 ] only one study (Deodari et al . [ 34 ]) was identified that described the CDI seasonality in children; therefore, generalizability of the findings may be limited among this population. Potential factors that may contribute to differences in monthly CDI incidence that could not be accounted for in this review, such as hospital characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing incidence of CDI among the paediatric population [ 33 ] only one study (Deodari et al . [ 34 ]) was identified that described the CDI seasonality in children; therefore, generalizability of the findings may be limited among this population. Potential factors that may contribute to differences in monthly CDI incidence that could not be accounted for in this review, such as hospital characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies included children aged 0-2 years (n=4), 0-5 years (n=2), 0-12 years (n=3) and 0-18 years (n= 22). The majority of studies were from North America (n=12; 6,184 cases) [13][14][15][16][17][18][19][20][21][22][23][24] and Europe (n=12; 2,467 cases) [8,[25][26][27][28][29][30][31][32][33][34][35], with other studies from Asia (n=4; 1,762 cases) [36][37][38][39], Australia (n=2; 148 cases) [40,41] and South America (n = 1; 210 cases) [42]. Ten studies included only community-onset patients [13,14,25,27,28,31,32,34,35,38], three included only hospital patients [20,30,40], 12 included both hospital and community [8, 15, 16, 19, 21-24, 26, 29, 33, 42] and six studies did not report the place of onset [17,…”
Section: Studies Included In the Analysismentioning
confidence: 99%
“…9 The diagnosis of bacterial AGE relies on stool cultures that have poor yield and high cost. 10,11 Therefore, a more careful selection of patients with a higher risk of bacterial infection may decrease costs and demand less labor in pediatric ED. Previous studies have attempted to predict which patients are at higher risk of bacterial AGE.…”
Section: Introductionmentioning
confidence: 99%